Reviewer Acknowledgements and Introduction of New Numbering Format: Special Edition from the Cirebon International Health Symposium - GHMJ (Global Health Management Journal), Volume 8, Number 1s, 2025 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal))
Starting from this edition, GHMJ (Global Health Management Journal) designates Special Editions with an “s” in the numbering (e.g., Vol. 8, No. 1s) to indicate their inclusion as a section within the ongoing issue, with all articles undergoing rigorous double-blind peer review to uphold the journal’s commitment to academic excellence. This issue of the Global Health Management Journal (Vol. 8, No. 1s, 2025) presents a diverse selection of articles reflecting the depth and breadth of current health research. From applied sciences, two studies examine the antimicrobial potential of mango peel extracts in inhibiting Staphylococcus aureus and Escherichia coli (‘Adawiyah et al., 2025; Siskanti et al., 2025), highlighting the value of natural resources in public health innovation. In the field of epidemiology and public health, important clinical insights are offered through studies on the relationship between antiretroviral therapy duration and kidney function in HIV/AIDS patients, as well as a retrospective review of psoriasis cases in Cirebon (Ayudhipasha et al., 2025; Putra et al., 2025).